Edukasi penyalahgunaan obat-obatan di kalangan remaja pada siswa siswi SMAN 1 Beruntung Baru - Yulianita Pratiwi Indah Lestari; Hendera; Mi'rajunnisa; Asyfa Putri Ramadhani; Cindy Cenora; Hilmalia; Malinda Apriliani; Muhammad Samawi (Universitas Mataram, 2023)
Teenagers today are getting used to the use of various illegal drugs, which aim to get temporary pleasure or as an escape from their problems. The use of various types of drugs in high doses causes various negative impacts for adolescents such as damage to the central nervous system, seizure disorders due to respiratory and heart muscle spasms, dehydration, heart attacks, and even a worse effect that cause death. In the residential environment, formal and non-formal figures are expected to participate actively in fostering and providing guidance and direction to young people. This outreach activity was carried out among teenagers so that they know and were aware of the consequences of drug abuse. This activity was expected to increase adolescent knowledge about illegal drugs. The implementation of counseling as one of the community service programs for the Faculty of Pharmacy Lecturers together with the D3 Pharmacy Students of the University of Muhammadiyah Banjarmasin at SMAN 1 Beruntung Baru entitled